NO STRESS METHODS FOR ASSESSING READING COMPREHENSION (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
The essay focuses on stress-free techniques for evaluating reading comprehension, highlighting learner-centered and anxiety-free strategies in language instruction. It explains how traditional assessment methods often put pressure on students, which prevents them from showing their actual comprehension, and suggests different approaches that incorporate evaluation into learning in a natural way. The article emphasizes methods such as using digital tools, keeping a reading diary, engaging in performance-based activities, creating visual representations, working together on projects, retelling stories, eliciting open-ended responses, and making informal observations. These strategies encourage intrinsic drive, support emotional well-being, and help readers connect more deeply with the material. In conclusion, the essay argues that stress-free evaluation methods foster confidence, creativity, and a lifelong good perspective about reading while also producing more precise data about students' understanding.